2017
DOI: 10.1088/1755-1315/90/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Risk-based approach in valuation of workplace injury rate for transportation and construction industry

Abstract: Abstract. The danger of injuries and accidents in various industries such as transportation and construction urges the government to control the occupational health and safety more strictly. However, in order to do so with the minimal costs modern risk management tools, have to be implemented. Risk-based approach is an essential tool for competent risk-assessment and used in a great variety of other countries, demonstrating great results in providing of safe working environment. The article describes the probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…94-FZ, through the holding of an auction (now expired in connection with the adoption of Federal Law No. 44-FZ of 05.04.2013 (edition of July 29, 2017) "On the contract system in the procurement of goods, works, services to ensure state and municipal needs " [19]). According to paragraph 2 of Part 1 of Art.…”
Section: Resultsmentioning
confidence: 99%
“…94-FZ, through the holding of an auction (now expired in connection with the adoption of Federal Law No. 44-FZ of 05.04.2013 (edition of July 29, 2017) "On the contract system in the procurement of goods, works, services to ensure state and municipal needs " [19]). According to paragraph 2 of Part 1 of Art.…”
Section: Resultsmentioning
confidence: 99%
“…This situation is often used by investors and developers who plan to erect objects of spot development: if the boundaries of the land plot are not indicated in the cadastral registration system, then, if necessary, the court decision can accelerate the procedure of surveying with neighboring houses, which leads to an additional problem of corruption of the executive bodies. On the basis of the foregoing, it can be concluded that infill development is inherently contrary to the idea of creating favorable living conditions for citizens and maintaining an ecologically normal habitat [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…There are a lot of researchers insisting on the development of riskbased approach in construction industry. It could demonstrate project benefits and will ease construction process for all of the participants due to publicly accessible information about companies and their experience [5]. The opportunities offered by the organization's risk management process help manager to achieve profitability and efficiency targets, as well as to prevent the irrational usage of resources.…”
Section: Methodsmentioning
confidence: 99%